REFLECTION OF SPIRITUAL AND MORAL IDEALS IN THE TEACHINGS OF KHOJA AHMAD YASSAVI AND SULAYMON BAKIRGANI (TAMADDUN NURI JURNALI, 2024)
This article discusses two prominent Sufi mystics, Khoja Ahmad Yassawi and Sulayman Boqirghani. The place of the "Yassawiyya" order and one of its prominent representatives, Sulayman Boqirghani, in the history of Sufism in Transoxiana, as well as the moral categories of self-control, strengthening of the will, and re-education of a person in their spiritual heritage, are revealed. In addition, their services in the development of Turkic Sufism and wisdom writing are revealed.